2004
DOI: 10.1063/1.1719279
|View full text |Cite
|
Sign up to set email alerts
|

Zinc oxide thin-film random lasers on silicon substrate

Abstract: Room-temperature ultraviolet lasing is demonstrated in mirrorless zinc oxide thin-film waveguides on (100) silicon substrate. Laser cavities, due to closed-loop optical scattering from the lateral facets of the irregular zinc oxide grains, are generated through the post-growth annealing of high-crystal-quality zinc oxide thin films obtained from the filtered cathodic vacuum arc technique. It is found that the lasing wavelength and linewidth of the zinc oxide random lasers under 355 nm optical excitation are ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
93
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 140 publications
(100 citation statements)
references
References 8 publications
7
93
0
Order By: Relevance
“…[1][2][3] ZnO is nontoxic, biocompatible, and low cost, making it a potential candidate for industrial applications. 4 ZnO films have been deposited by different techniques such as chemical vapor deposition, 5 vacuum evaporation, 6 radiofrequency (RF) sputtering, 7 solgel, 8 molecular-beam epitaxy, 9 pulsed laser deposition, 10 atomic layer deposition, 11 chemical vapor deposition, 12 vacuum arc technique, 13 and spray pyrolysis. 14 Among these techniques, the spray pyrolysis method possesses the advantages of high deposition rate with good control of the physical properties of the deposited layers and production of large-area device-quality material.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] ZnO is nontoxic, biocompatible, and low cost, making it a potential candidate for industrial applications. 4 ZnO films have been deposited by different techniques such as chemical vapor deposition, 5 vacuum evaporation, 6 radiofrequency (RF) sputtering, 7 solgel, 8 molecular-beam epitaxy, 9 pulsed laser deposition, 10 atomic layer deposition, 11 chemical vapor deposition, 12 vacuum arc technique, 13 and spray pyrolysis. 14 Among these techniques, the spray pyrolysis method possesses the advantages of high deposition rate with good control of the physical properties of the deposited layers and production of large-area device-quality material.…”
Section: Introductionmentioning
confidence: 99%
“…Two ZnO epilayers, sample A (ZnO(100 nm)/ SiO 2 (400 nm)/Si (substrate)) and sample B (ZnO(100 nm)/ MgO(200 nm)/ZnO(100 nm)/SiO 2 (400 nm)/Si (substrate)), were fabricated by the filtered cathodic vacuum arc technique and thermal annealing. [4,5] It is shown that the top (002)-oriented ZnO active layer of sample A (sample B) experiences tensile (compressive) strain along the c-axis.[5] Figure 1 shows the lasing spectra versus temperature, T, for the two samples under optical excitation at ∼ 2 × I th , where I th is the pump threshold intensity at the corresponding T. It can be shown that sample A (sample B) demonstrates RT EHP (FE) radiative recombination with discrete peaks at ∼ 393 nm (∼ 380 nm), and the corresponding lasing mechanism is attributed to random laser action. [5] With the increase of temperature, the shrinkage of the bandgap red-shifts the lasing peaks.…”
mentioning
confidence: 97%
“…Investigations of the temperature dependence of stimulated EES emission of the ZnO films on sapphire and the ZnO/ (Mg, Zn)O superlattices on ScAlMgO 4 have found that the corresponding T c values are 67 and 87 K, respectively. [7] These samples (i.e., without grain boundaries) show smaller values of T c (i.e., poorer high-T performance) than those of our ZnO epilayers.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…This is because the use of random media will avoid the difficulty of cleaving smooth facets from the ZnO material in order to sustain lasing, leading to low-cost, high-volume fabrication of UV laser diodes. [2] Recently, we have demonstrated effective UV random lasing from patterned ZnO-SiO 2 nanocomposite films under optical excitation. UV random lasing can be achieved in these films because the appropriate patterning of ZnO clusters enhances the optical quality (i.e., higher gain and lower loss) of the random media.…”
mentioning
confidence: 99%